Female urethral injuries associated with pelvic fracture: a systematic review of the literature. (7th September 2017) - Patel, Devin N.; Fok, Cynthia S.; Webster, George D.; Anger, Jennifer T.
Abstract : To review systematically the literature on female urethral injuries associated with pelvic fracture and to determine the optimum management of this rare injury. Using Meta‐analysis of Observational Studies in Epidemiology criteria, we searched the Cochrane, Pubmed and OVID databases for all articles available before 30 June 2016 using the terms 'female pelvic fracture urethroplasty', 'female urethral distraction', 'female pelvic fracture urethral injury' and 'female pelvic fracture urethra girls.' Two authors of this paper independently reviewed the titles, abstracts, and articles in duplicate. We identified 162 individual articles from the databases. Fifty‐one articles met our criteria for full review, including 158 female patients with urethral trauma. Of these injuries, 83 (53%) were managed with immediate repair; 17/83 (20%) via primary alignment and 66/83 (80%) via anastomotic repair. The remaining 75/158 (47%) were managed with delayed repair. Rates of urethral stenosis and fistula were highest after primary alignment. Urethral integrity appears to be similar after both primary anastomosis and delayed repair; however, patients experienced significantly more incontinence and vaginal stenosis after delayed repair. Patients who underwent delayed urethral repair were more likely to undergo more extensive reconstructive surgery than those who underwent primary repair. The optimum management of female urethral distraction defects is based on very‐low‐quality literature. Based on our review of the available literature, primary anastomotic repair of a female urethral distraction defect via a vaginal approach as soon as the patient is haemodynamically stable appears to be optimal.